TB-related technical enquiries received at the Research Institute of Tuberculosis, Japan, during COVID-19 - M. Urakawa; A. Yasukawa; S. Hirao; M. Ota; Y. Hatamoto; T. Zama; Y. Nagata; T. Yoshiyama (The Union, 2024)
SETTING: Japan: a low-TB-burden country. OBJECTIVE: To characterise TB-related technical enquiries received in 2020-2022, and share the lessons learnt. DESIGN: This was a descriptive study. RESULTS: We received 1,898 communications, of which 1,447 (40.2 per month) were classified as technical enquiries, 34% fewer than the 2,197 enquiries received in 2017-2019. The enquiry rates were highest for Shimane (4.32/100,000 population) and Yamanashi (2.59/100,000 population) prefectures, and lowest in Ehime (0.00/100,000 population) and Yamagata (0.09/100,000 population) prefectures. The main organisations the enquirers belonged to were local governments (n = 989, 68.3%) and healthcare facilities (n = 242, 16.7%). The enquirers included medical doctors (n = 236, 16.3%), nurses (n = 814, 56.3%), and the general public (n = 141, 9.7%). The most frequent enquiries were about TB diagnosis and treatment, including laboratory diagnosis (n = 442, 30.6%), followed by the regulatory framework (n = 216, 14.9%), contact investigation (n = 151, 10.8%), and TB in foreigners (n = 112, 7.9%). CONCLUSION: During the COVID-19 era, we received two-thirds of technical enquiries compared with 2017-2019, because local health offices were overwhelmed by the pandemic. Since the most frequent enquiries were about diagnosis and treatment of TB, the health ministry of Japan should maintain a few specialised TB institutions with TB physicians to provide technical assistance.